From core-shell to Janus: Microfluidic preparation and morphology transition of Gas/Oil/Water emulsions. (23rd November 2017) - Zhang, Shao-Bin; Ge, Xue-Hui; Geng, Yu-Hao; Luo, Guang-Sheng; Chen, Jian; Xu, Jian-Hong
Highlights: A novel and simple strategy to produce Gas/Oil/Water emulsions with controlled morphologies is developed. We achieved the morphology transition of Gas/Oil/Water emulsions: from core-shell to Janus. The morphology of Janus droplets can be tuned by changing several parameters. Abstract: In this article, gas-liquid-liquid emulsion drops were firstly generated by one-step method in a coaxial microfluidic device. Based on that, the effects of several parameters on the morphology transition from core-shell to Janus droplets was studied systematically. By tuning flow rates, interfacial tensions and viscosity, we can change the size and morphology of droplets. Furthermore, non-spherical microparticles were obtained by using photo-responsive reagent through solidification. The developed approach offers a novel and simple strategy on the synthesis of Janus emulsions and anisotropic microparticles with controlled morphologies.